Recent advances in using of chitosan-based adsorbents for removal of pharmaceutical contaminants: A review - Karimi-Maleh, Hassan; Ayati, Ali; Davoodi, Reza; Tanhaei, Bahareh; Karimi, Fatemeh; Malekmohammadi, Samira; Orooji, Yasin; Fu, Li; Sillanpää, Mika (Journal of cleaner production, 2021)
During recent years, the pharmaceutical compounds have been considered as an emerging water micro-pollutant, due to their potential eco-toxicity. Among the various treatment approaches, the adsorption method has been found an attractive, simple and powerful tool for the removal of these compounds. Recently, the chitosan-based materials (composite), as an eco-friendly biopolymers class, show remarkable promise for effective adsorption of these compounds. This paper aims to establish criteria for choosing the finest chitosan-derivatives through a critical review and assess the published researches dealing with the effectiveness of them in the adsorptive removal of pharmaceutical compounds. This is followed by a preliminary summary for pharmaceutical contaminants adsorption performance of studied chitosan-based materials in tables. In this review article, the pharmaceutical materials also introduced into three categories as antibiotics (tetracycline, amoxicillin, etc.), non-steroidal anti-inflammatory (diclofenac, ibuprofen, etc.) and other pharmaceutical compounds (hydroquinone, fluoxetine, etc.), and the employed adsorbents for their removal were studied. This review provides information for the development of composite adsorbents, enhancement of adsorption ability by modification with different functional groups, real wastewater treatment, multicomponent adsorption, regeneration enhancement and fixed-bed studies which is helpful for readers to water and wastewater treatment process at both laboratory and field scales. Along this line, the impact of the various parameters (pH, sorbent amount, initial concentration, temperature, etc.) and the adsorption mechanism are also briefly discussed. [Display omitted] •Pharmaceutical compounds have been considered as an emerging water micro-pollutants.•Chitosan-based materials are promising as drug adsorbents in removal investigations.•pH, temperature and ionic strength were found as the most effective parameters.